Between objects and lives: Exploring ethics in pathological museums and collections (Cadernos de Sociomuseologia, 2023)
This article addresses the complex intersection between ethics, museums and pathology collections through a historical analysis that dates back to the 18th century, when medical ethics began to be codified. The text explores the current context, where ethical concerns expand to the medical collections. The objective of this article is to analyze the complex ethical issues involved in the preservation and exhibition of human remains in museums and medical collections, considering historical developments, contemporary challenges and the need for a contextualized ethical approach. To achieve this objective, a methodology was adopted that combines historical research, critical analysis of academic literature and ethical reflection addressing issues related to the preservation and exhibition of human remains in museums and medical collections. Some of the results achieved in this critical analysis include identifying the lack of common guidelines for dealing with human remains in museums, highlighting the delicate balance between conservation and access. It is argued that an effective ethical approach must recognize the complexity of human remains, considering them both as scientific objects and as lived lives, and emphasizes the importance of historical contextualization to ethically discern the treatment of these collections. Ultimately, it is concluded that medical ethics and museological approaches are subject to continuous change, highlighting the importance of keeping up with transformations in the field.KEY WORDS: Deontology; Scientific heritage; Museology